Implementasi Low Power pada Sistem Notifikasi Kantuk pada Pengemudi menggunakan Finite-State Machine berbasis Arduino - Muhammad Irvine Fidellio Maiza; Agung Setia Budi; Dahnial Syauqy (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Every year, the death rate caused by traffic accidents increases sharply. One of the biggest causes of traffic accidents is drowsiness experienced by vehicle drivers. Therefore, researchers are interested in developing a drowsiness detection system using low power in the hope of reducing the rate of traffic accidents caused by drowsiness. The system is designed using the FC-51 Infrared sensor embedded in the glasses as a detection of the driver's eyelid position. The system is built with a threshold parameter that can be reconfigured such as the duration of closed eyelids. This system is also built using a finite-state machine algorithm, where this algorithm will create several states with different operational modes. One of these states is the Low Power On state to save power. This is necessary because the system will work continuously. In the Low Power On state, the method used to save power usage is to make the 800L SIM module enter sleep mode by slowing down the clock its used. The system will send a notification in the form of a buzzer and an SMS message containing the driver's coordinates to relatives when sleepiness is detected. From the results of the tests that have been carried out, it is concluded that the system can carry out each of its functionalities and succeeded in reducing the use of current consumption by 30% when in the Low Power On state.